Western Mesoamerican Calendars and Writing Systems Proceedings of the Copenhagen Roundtable - Clemmensen, Mikkel Bøg; Helmke, Christophe (2023)
Western Mesoamerican Calendars and Writing Systems draws together studies by some of the world's leading experts presented at a conference held in December 2020, 'The Origins and Developments of Central Mexican Calendars and Writing Systems'. Mesoamerica is one of the few places to witness the independent invention of writing. From the earliest attestations of this intellectual feat in the Late Preclassic period 900 bc-ad 150), writing spread throughout Mesoamerica, developing and diversifying into a series of distinct and independent scripts. With the exception of the celebrated phonetic decipherments of Maya and Aztec writing, which are now well-documented and can be fully read, most Mesoamerican writing systems remain little studied and undeciphered. This is particularly true of the writing systems of Western Mesoamerica, the topic of this volume.Bringing together new research on Western Mesoamerican writing systems, some contributions focus on specific features of a given writing system, whereas others offer state-of-the-art syntheses of whole writing systems. Two contributions focus on the calendar in particular, and associated notations, as integral parts of writing systems. Chapters are included on the writing system of Teotihuacan, the Ñuiñe writing of the Mixteca Baja and adjoining areas, the writing system of the Epiclassic period and Aztec writing of the Postclassic. These writing systems represent more than a millennium of written records and literacy in Mesoamerica, spanning from the Early Classic to the Late Postclassic (from the 2nd to the sixteenth centuries ad). Aztec writing even continued in use for several decades after the Spanish invasion of Mexico (ad 1519-1521), which saw the introduction of the Latin alphabet and the gradual obsolescence of Mesoamerican logophonetic writing systems.